2016
DOI: 10.1080/10376178.2016.1221324
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and spiritual care: a descriptive survey of nursing practices in Turkey

Abstract: Our research findings suggest that there is a lack of knowledge and general confusion regarding Turkish nurses perceptions and practices related to spiritual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
2
15
0
1
Order By: Relevance
“…There was a statistically significant increase in knowledge, self-confidence, and competence in nurses who had attended a workshop on spiritual care [52]. Other authors imply that there is insufficient knowledge and training regarding nurses' perceptions and nursing practice related to spiritual care, which results in general confusion [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…There was a statistically significant increase in knowledge, self-confidence, and competence in nurses who had attended a workshop on spiritual care [52]. Other authors imply that there is insufficient knowledge and training regarding nurses' perceptions and nursing practice related to spiritual care, which results in general confusion [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore essential to synthesise both older adults’ and nurses’ or caregivers’ views to determine the spiritual care provided in RCF. Even though the provision of spiritual care to patients is acknowledged by many as an important component of nursing care in general (Akgün Şahin & Kardaş Özdemir, ; Cockell & McSherry, ; McSherry & Jamieson, ; Melhem et al., ; Mónica, Lucy Muñoz de, Claudia, & Sandra, ), there is limited evidence specific to spiritual care of older adults, particularly those living in RCF. Furthermore, practical aspects of spiritual needs assessment and spiritual care provision remain underexplored.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the mean spiritual care therapeutics scale score of the nurses was 41.92 ± 10.46 and they had a medium level of frequency of the provision of spiritual care therapeutics. Likewise, in the literature, Akgün ( 2016 ) reported that nurses had a medium level of frequency of the provision of spiritual care therapeutics. In contrast, some studies have suggested that nurses have a low frequency of providing spiritual care therapeutics (Mamier 2019 ; Taylor et al 2019 ; Taylor et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%